East Asian regional cooperation : Japan falling behind China? - Mushahid Ali (2013)
Japan, which previously had a leading role in Southeast Asian regional cooperation, seems to have fallen behind China in recent decades. However it is still a crucial economic player and can balance China politically in regional forums.